Analysis of Nun Sukun and Tanwin Reading Errors in 5th Grade MI Students in Tahsin Learning: Research at MI Sindang Sari - Salsabila Defika; Saila Faroh; Nanda Alya; Muhamad Ibnu Malik (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the forms of errors in reading nun sukun and tanwin, the factors causing these errors, and the tahsin learning strategies implemented by teachers to overcome them among fifth-grade students at Madrasah Ibtidaiyah (MI) Sindang Sari. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings reveal that students frequently made errors in applying the rules of idgham, ikhfa’, iqlab, and idzhar. The causes of these errors include internal factors such as limited understanding of tajwid and lack of regular Qur’anic reading practice, as well as external factors including differences in students’ initial abilities, limited instructional time, and monotonous teaching methods. To address these issues, tahsin teachers applied strategies such as providing correct reading models, habituation through repetitive practice, individual guidance and correction, and periodic evaluation. These strategies gradually reduced students’ reading errors and improved the quality of Qur’anic recitation in accordance with tajwid rules.